Ritme Bisnis Digital: Dinamika Transaksi Online Jesika Shop Kebonagung Dalam Konteks Ekonomi Islam - Agus Tohawi; Juni Iswanto; Subekan Subekan; Alfin Yuli Dianto; Bhaswarendra Guntur Hendratri (Departement of Mathematics Education, 2023)
This study explores the online buying and selling transactions at Jesika Shop Kebonagung, focusing on the aspects of contracts (akad), Islamic economics, and problem-solving strategies. Jesika Shop Kebonagung, as an online store, exhibits a transaction process involving marketing through social media, product selection, buyer information input, payment methods, and product delivery. The Islamic economic review highlights the utilization of Salam and Wakalah Bi Al-Ujrah contracts. Strategies to address issues involve active communication between sellers and buyers through various social media platforms, recommendations for transactions through applications with shipping cost subsidies, and offers of discounted shipping promotions. The research methodology employed is qualitative descriptive, utilizing observation, interviews, and documentation. The research findings provide comprehensive insights into the online buying and selling practices of Jesika Shop Kebonagung from the perspective of Islamic economics.